Combined Application of Tacrolimus with Cyproconazole, Hymexazol and Novel {2-(3-R-1H-1,2,4-triazol-5-yl) phenyl}amines as Antifungals: In Vitro Growth Inhibition and In Silico Molecular Docking Analysis to Fungal Chitin Deacetylase - Antypenko, L.; Meyer, F.; Sadyk, Zh.; Shabelnyk, K. P.; Kovalenko, S. I.; Steffens, K. G.; Garbe, L. A.; Шабельник, Костянтин Петрович; Коваленко, Сергій Іванович (My University, 2023)
Abstract: Agents with antifungal activity play a vital role as therapeutics in health care, as do fungicides in agriculture. Effectiveness, toxicological profile, and eco-friendliness are among the properties used to select suitable substances. Furthermore, a steady supply of new agents with different modes of action is required to counter the well-known potential of human and phytopathogenic fungi to develop resistance against established antifungals. Here, we use an in vitro growth assay to investigate the activity of the calcineurin inhibitor tacrolimus in combination with the commercial fungicides cyproconazole and hymexazol, as well as with two earlier reported novel {2-(3-R-1H-1,2,4-triazol-5-yl)phenyl}amines, against the fungi Aspergillus niger, Colletotrichum higginsianum, Fusarium oxysporum and the oomycete Phytophthora infestans, which are notoriously harmful in agriculture. When tacrolimus was added in a concentration range from 0.25 to 25 mg/L to the tested antifungals (at a fixed concentration of 25 or 50 mg/L), the inhibitory activities were distinctly enhanced. Molecular docking calculations revealed triazole derivative 5, (2-(3-adamantan- 1-yl)-1H-1,2,4-triazol-5-yl)-4-chloroaniline), as a potent inhibitor of chitin deacetylases (CDA) of Aspergillus nidulans and A. niger (AnCDA and AngCDA, respectively), which was stronger than the previously reported polyoxorin D, J075-4187, and chitotriose. The results are discussed in the context of potential synergism and molecular mode of action.
Keywords: tacrolimus; synergism; hymexazol; cyproconazole; {2-(3-R-1H-1,2,4-triazol-5-yl)phenyl} amines; A. niger; C. higginsianum; F. oxysporum; P. infestans; chitin deacetylase